LO072: Fever in the returning traveller: a systematic review and critical appraisal of existing clinical practice guidelines and approaches to returning travellers presenting with fever. (2nd June 2016) - Collier, A.; Perry, J.J.; Nath, A.
Abstract : Introduction: Fever in the returning traveller is a common ED presentation; however approaches and level of comfort with tropical diseases vary widely. This project aimed to conduct a systematic review and critical appraisal of existing clinical practice guidelines and approaches, to guide an ED approach, in Canada, to fever in the returning traveller.Methods: A literature review was conducted of peer reviewed papers, national and international practice guidelines, and practice statements presenting approaches to fever in the returning traveller. A literature search was conducted using MEDLINE and Embase (1947-Dec 2014), with librarian assistance to optimize strategy. The databases of guideline clearing houses, CMA, PHAC, WHO, CDC, and the Cochrane library were searched, along with a google scholar search. References of included articles were hand searched. Article titles and abstracts were reviewed by the author for inclusion. Key elements of the guidelines and approaches were identified and grouped by theme and where appropriate, the quality of guidelines were assessed by two reviewers using the AGREEII tool.Results: The search returned 1598 titles. 72 full manuscripts were reviewed based on inclusion from title and abstract, with 24 manuscripts included for final analysis. Common elements suggested by the guidelines or approaches were identified and grouped within three themes (key historical features, physical exam findings, investigations). Most manuscripts presented tables of important clinical information, but limited guidance on how to approach diagnosis in a focused manner. When evaluated by AGREEII, only one guideline (D'Acremont et al) scored > 50% overall quality rating. Unlike other approaches, this guideline proposes a stepwise approach to diagnosis and treatment based on the presence of key exposures, signs/symptoms, and eosinophilia.Conclusion: The guideline by D'Acremont et al was identified as the most rigorous existing practice guideline. This guideline, combined with other elements identified by thematic review, forms the basis of a suggested ED approach to fever in the returning traveller, which will be further refined using the AGREEII model to propose a practice guideline for Canadian EDs.